TANTANGAN PENGEMBANGAN PARIWISATA DI DAERAH PINGGIRAN - I Made Adikampana (Institut Pariwisata dan Bisnis Internasional, 2014)
Â Â Â Â Â Â Â Â Â Â Â The development of tourism in peripheral areas is seen as a product diversification in the tourism destination and an appropriate strategy for developing the peripheral areas itself. Tourism is considered to address the main issues of development in peripheral areas, themselves particularly unemployment and urbanization. However, there are challenges of tourism development in peripheral areas due to the relationship with the center of tourism development areas.Â Â Â Â Â Â Â Â Â Â Â Based on the case of tourism development in â€œTaman Nasional Bali Baratâ€ (TNBB), this article examines the challenges of tourism development in peripheral areas. The examination showed that tourism in TNBB has a dependence on the center of tourism development in Bali. This is shown that the economic impact of tourism in TNBB toward local community has not been significant. Tourism in TNBB have not been able to diversify the economic based of local community, so that the surrounding communities in TNBB still depends on the utilization of natural resources in the conservation area.Â